Análise de imagens tomográficas da Ciência do Solo em ambiente de realidade virtual - Botega, Leonardo Castro (2008)
This work presents a Virtual Reality environment dedicated to the analysis of tomographic images of Soil Science. Its architecture uses models proceeding from a volumetric (3-D) reconstruction algorithm, summed with several graphics processes of manipulation and visualization, in a way to provide immersion and interaction of the user with the virtual scene. Its validation was performed based on a case study involving the analysis of the porosity of the agricultural soil samples, which presents preferential paths for the water and solute flow (fingering). Results illustrate the consistent verification of the preferential paths of the agricultural soil samples, analyzed based on the developed environment.